Penggunaan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu di Kelas 5 SD - Risda Silvia; Zuryanty Zuryanty (Innovative: Journal Of Social Science Research, 2023)
The fact that Class V students at SD Negeri 17 Sungai Pandahan still have low learning outcomes is the basis of this research. This happens as a result of the learning process that does not work as it should. By using the Cooperative Learning Type Two Stay Two Stray (TSTS) model, this study seeks to describe the increase in student learning outcomes. Classroom Action Research uses qualitative and quantitative methods, the type of research is PTK. The test subjects were teachers and students of grade V. Results increased from cycle I to cycle II, planning from 82.05% to 94.44%. Educator activity from 79.69% to 90.63%. Student activity from 78.18% to 90.63%. And the learning outcomes of knowledge from 77.3 increased to 90.1, in the skill aspect scores from 76.5 to 86. It was concluded that the TSTS type Cooperative Learning model could improve student learning outcomes.